PERAWATAN MESIN PEMERAH SUSU SAPI PORTABLE MODEL BODYPACK - Roni Suhartono; Adhan Efendi (LPPM Politeknik LP3I Medan, 2020)
Cow milking machines are used to help farmers in mountainous areas in the milking process. The problem faced is that it takes a schedule and selection of appropriate engine maintenance methods so that the milking machine for cows is not easily damaged. This study aims to make a schedule and determine the engine components that must be treated. The data obtained are then processed descriptively qualitatively. The results of the study concluded: (1) the maintenance of a portable milking machine with a bodypack model is carried out every day using the Inspection, Small Repair, Medium Repair, and Overhaul (ISMO) methods; (2) the main components to be examined are the electrical parts of the machine, the machine box, the putting straw, the milk container, and the carrying case; (3) routine maintenance carried out is proven to be able to maintain and extend the life of the portable milking machine model bodypack